Pengaruh Kepuasan Kerja terhadap Loyalitas Staf Reception pada Hotel X di Madiun Jawa Timur - Basalamah, Anwar (Binus Business Review, 2012)
Reception staff loyalty is much influenced by several factors, one of them is job satisfaction. Employee job satisfaction plays important role in creating employee loyalty. For hoteliers who serve as provider of accommodation services, the demand for the creation of quality human resources is maximum achievement. One of the important section in the front office is receptionist. Today, hoteliers pay very close attention because the employee turnover will certainly affect the consistency of services offered by the hotel. Therefore, the hotel is getting active in increasing the satisfaction of its staff in order to minimize employee turnover especially in a very important role such the receptionist. Although the validity of the relationship between job satisfaction and reception staff loyalty is still an exciting debate, the result of the research conducted in the Hotel X is expected to help increase employee satisfaction in order to create quality of life that will improve labor productivity.